How do we learn professional ethics? Professional competences, embodiment and ethics in physiotherapy education in Norway - Dahl-Michelsen, Tone; Groven, Karen Synne (Critical Studies in Teaching and Learning, 2023)
This  paper  aims  to  enhance the  understanding  of how  physiotherapy  students  develop professional  ethical  insight. The empirical data is based on  participant  observations  and  in-depth interviews with first-year students attending skills training classes in one of Norway’s four physiotherapy bachelor programmes. Theoretically, this paper is framed within Merleau-Ponty’s and Daly’s embodied approaches to ethics. The analysis pays special attention to the concepts of ethical insight, ethical sensibility and hyper-reflection. The findings are presented according to two themes: ‘embodying  tacit  care’ and ‘in-between abstract  and  embodied ethics’. In the discussion, we address students’ development of ethical sensibility and lack of hyper-reflection  skills.  Ultimately,  we  argue  that  while  physiotherapy  education  should embrace the unique nature of skills training as an opportunity to stimulate students to develop their  ethical sensibility,  at  the  same  time, the  curriculum  must  also emphasise  hyper-reflection  (critical  thinking).  We also discuss how educators can organise their  curriculum and teaching in a way that enhances the potential for students to develop professional ethical insight